Efficacy and safety of immune checkpoint inhibitors for EGFR mutated non-small cell lung cancer: a network meta-analysis - Zhu, Lin; He, Wenjuan; Xie, Cunlei; Shu, Yang; Zhang, Chunxia; Zhu, Yawen (Frontiers in Immunology, 2024)
IntroductionNon-small cell lung cancer (NSCLC) constitutes approximately 80–85% of cancer-related fatalities globally, and direct and indirect comparisons of various therapies for NSCLC are lacking. In this study, we aimed to compare the efficacy and safety of immune checkpoint inhibitors (ICIs) in patients with epidermal growth factor receptor (EGFR)-mutated NSCLC.MethodsThe electronic databases were systematically searched from inception until March 18, 2024. Studies comparing two or more treatments involving ICIs in patients with EGFR-mutated NSCLC were included. The primary endpoints were overall survival (OS) and progression-free survival (PFS), and the secondary endpoints were overall response rate (ORR), any grade adverse events (AEs), grade ≥3 AEs, and AEs requiring treatment discontinuation. The R software with the gemtc package was used to compare the outcomes of the different treatments.ResultsIn 11 eligible studies involving 1462 patients and 5 regimens (chemotherapy [chemo], ICI, ICI+chemo, antiangiogenesis+chemo, and ICI+antiangiogenesis+chemo), ICI+antiangiogenesis+chemo achieved the most favorable OS compared to chemo (HR=0.74, 95% CI 0.41–1.23), ICI+chemo (HR=0.94, 95% CI 0.57–1.46), and ICI (HR=0.58, 95% CI 0.27–1.08) and a nearly equivalent effect to antiangiogenesis+chemo (HR=1.01, 95% CI 0.52–1.92). The PFS and ORR results were similar to those of OS. ICI monotherapy exhibited the lowest toxicity profile.ConclusionsThese findings indicate that ICI+antiangiogenesis+chemo may be potentially beneficial for patients with EGFR-mutated NSCLC. However, the observed difference was not significant; thus, more studies are needed to confirm the efficacy and safety of the combined ICI treatment strategy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023424781.